Evaluating the learning goal attainment in Nihongo Noryoku Shiken N5 course - Ai Sumirah Setiawati; Wagiran Wagiran; Subyantoro Subyantoro (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
The objective of the study is to evaluate the learning implementation of the Nihongo Noryoku Shiken N5 course as a new course offered in the 2020 curriculum at the Japanese Language Education Study Program in UNNES. A goal-oriented evaluation model by Tyler was employed in the evaluation process to measure how far the learning goals that have been determined at the beginning of the lecture are achieved. This evaluative research relied on a quantitative descriptive approach; its steps comprised (1) data collection, (2) data processing and analysis, and (3) recommendation formulation. According to the evaluation results, the learning goals of Nihongo Noryoku Shiken N5 had been met, although it was not that significant. Several conditions cause such issues. (1) In the class, some students had good Japanese language skills; they claimed that the lesson was too easy, so their progress was not significant. (2) The evaluation instruments were not valid. (3) Other conditions, e.g., the implementation of online learning and tests, hindered classroom activities and monitoring. Improving the teaching and learning materials and evaluation instruments is recommended. Furthermore, some additions to the curriculum need to be considered, such as adding the credits for the grammar or Bunpo course.